Insights into 3D printing in medical applications - Sun, Zhonghua (AME Publishing Company, 2019)
Three-dimensional (3D) printing has been increasingly used in the medical field with reported applications showing great value in assisting clinical decision-making and improving patient care (1-10). Patient-specific 3D printed models derived from medical imaging datasets, mainly from computed tomography (CT) and magnetic resonance imaging (MRI) are shown to play an important role in pre-surgical planning and simulation of complex surgical procedures, medical education and patient-doctor communication (1-14).